The microplastic pollution in beaches that served as historical nesting grounds for green turtles on Hainan Island, China. (December 2021) - Zhang, Ting; Lin, Liu; Li, Deqin; Wu, Shannan; Kong, Li; Wang, Jichao; Shi, Haitao
Abstract: This study evaluated microplastic pollution in beaches that have served as historical nesting grounds for green turtles in Hainan Island, China and explored the sources of microplastic pollutants to conduct habitat restoration for sea turtles. The average abundance of the microplastics in the beach surface sediments was 2567.38 ± 2937.37 pieces·m −2 or 641.85 ± 734.34 thousand pieces·m −3, foam and plastic block were the main microplastics identified. Microplastic size was predominantly within the 0.05–1 mm category (small microplastic particles), and most microplastic particles were white. Polystyrene and polyethylene were the dominant plastic compositions. The type and compositions of microplastics indicate that most microplastics in this study were broken from large plastic blocks and foam. To reduce the threat of microplastic pollution to marine life, including sea turtles, we suggested removing plastic litter, especially small plastic on beaches, and replacing and recovering the foam used in aquaculture before it ages and fragments. Highlights: Microplastic were found in all beaches that served as historical nesting grounds for green turtles in Hainan Island, China. Polystyrene and polyethylene were the dominant compositions of microplastic in this study. Microplastic size was mostly in 0.05–1 mm (small microplastic particles), and the color of microplastic was mostly white. Removing small plastic litter and replacing and recovering the foam maybe can reduce microplastic pollution.